Formulation and Evaluation of Repaglinide Buccal Tablet: Ex Vivo Bioadhesion Study and Ex Vivo Permeability Study - Biswajit Biswal, Nabin Karna, Bhavesh Bhavsar (Journal of Applied Pharmaceutical Science, 2014)
The present work was performed to develop and evaluate buccal tablet containing antidiabetic drug (Repaglinide). Ethyl cellulose was used as backing membrane and Carbopol 934p, Polyox wsr N-80 NF, HEC and HPC was used as bucco adhesive polymer. Aspartame was used as sweetener. Thickness, Hardness, weight variation and drug uniformity were investigated. The tablet formulations were also subjected to drug release in 250ml 6.8 phosphate buffer. Ex vivo bioadhesion, retention time and permeation through porcine buccal mucosa membrane. Effects of different bucco adhesive polymer were evaluated on release and bioadhesion, retention time and permeation of drugs. F5 formulations showed maximum amounts of drugs release (87.18%) at the end of 10 h dissolution study. F5 also showed maximum bioadheion (0.0754N) and the resident time of F5 formulation was 9.2 h. It shows 41.52% drug release after 10 h permeation study through porcine buccal mucosa mounted in Franz cell. The tablet also found stable in human saliva after 10hr. The tablet was not showed any type of physical changes after the completion of 10 h. The results of the study suggested that new buccal tablet formulations of combined bucco adhesive polymers can be suitably developed as an alternate to conventional dosage forms.
Keywords: Repaglinide, Buccal Tablet, ex vivo Bioadhesion, Franz Diffusion Cell.